1995
DOI: 10.1006/qres.1995.1081
|View full text |Cite
|
Sign up to set email alerts
|

Improving in Situ Cosmogenic Chronometers

Abstract: New radiocarbon ages for Sierra Nevada deglaciation, the first 10 Be measurements from the Laurentide terminal moraine, and calculations based on paleomagnetic field strength have the potential to substantially improve the accuracy of cosmogenic age estimates. Specifically, three new constraints apply to the interpretation of measured abundances of in situ produced cosmogenic 10Be and 26Al: (1) A suite of minimum-limiting radiocarbon dates indicates that the Sierra Nevada was deglaciated at least several thous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 0 publications
1
61
0
Order By: Relevance
“…The chosen production rate of 5.55 atoms/g•qtz is ~7% higher than short-term rates calibrated from samples ≤ 13 ka old and ~7% lower than modeled and calibrated rates for timescales of millions of years, so is considered appropriate for timescales of tens to few millions of years (Perg et al, 2001;Clark et al, 1995). Empirically, choosing a higher or lower production rate from among accepted values changes resulting model ages by no more than about 10%.…”
Section: Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The chosen production rate of 5.55 atoms/g•qtz is ~7% higher than short-term rates calibrated from samples ≤ 13 ka old and ~7% lower than modeled and calibrated rates for timescales of millions of years, so is considered appropriate for timescales of tens to few millions of years (Perg et al, 2001;Clark et al, 1995). Empirically, choosing a higher or lower production rate from among accepted values changes resulting model ages by no more than about 10%.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…10 Be production rates are constrained by models (Masarik and Reedy, 1995), using measured neutron and muon fluxes (Dunai, 2000), by direct measurement in artificial targets (Nishiizumi et al, 1996), and by calibration against deposits with independent age constraint (Nishiizumi et al, 1986;Brown et al, 1991;Clark et al, 1995). The production rate at any given location fluctuates due to changes in solar output, geomagnetic field configuration, and atmospheric density (Dunai, 2000;Bierman, 1994).…”
Section: Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zero-erosion model ages were calculated using a sea level high-latitude (SLHL) 10 Be production rate of 5.06 atoms/g quartz/yr. This production rate is based on measurements of glacial surfaces in the Sierra Nevada by Nishiizumi et al [1989] recalculated using the revised 13,000 years glacial retreat ages reported by Clark et al [1995], and rescaled for latitude and altitude using the coefficients of Lal [1991], as described by Owen et al [2002]. An uncertainty of 6% on the production rates [Stone, 2000] is considered.…”
Section: Appendix B: Sampling and Cosmogenic Datingmentioning
confidence: 99%
“…These production rates were used for consistency with previous reports of erosion rates or exposure ages, despite the growing debate over production rates (e.g. Clark et al, 1995;Nishiizumi et al, 1996;Stone et al, 1998a;Dunai, 2000) and the potential contribution of muons to nuclide concentrations under moderate and high erosion rates (e.g. Brown et al, 1995;Stone et al, 1998b;Granger and Smith, in press).…”
Section: Cosmogenic Nuclidesmentioning
confidence: 99%